1982
DOI: 10.1126/science.7079738
|View full text |Cite
|
Sign up to set email alerts
|

Lipofuscin: Resolution of Discrepant Fluorescence Data

Abstract: Lipofuscin granules (age pigments) emit yellow light under ultraviolet excitation in the fluorescence microscope. The reported blue emission maximum of extracts of lipofuscin-laden cells may result from instrumental bias. The major fluorescent components that accumulate with age in these lysosomal residual bodies of human retinal pigment epithelium are yellow-emitting fluorophores. Different age-related fluorophores, which do emit blue light, are derived from other intracellular sources. A reevaluation of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
65
0

Year Published

1982
1982
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(72 citation statements)
references
References 24 publications
5
65
0
Order By: Relevance
“…Nelson and Morton, 1979;Moore et al, 1980;Mathew and Damodaran, 1997), crustaceans (e.g. Sheehy, 1989;Wahle et al, 1996;Medina et al, 2000;Bluhm et al, 2001a,b) and vertebrates (Eldred et al, 1982). This supports the view that the connective tissue granules in E. exalbida are lipofuscin.…”
Section: Is the Substance Found In E Exalbida Lipofuscin?supporting
confidence: 72%
“…Nelson and Morton, 1979;Moore et al, 1980;Mathew and Damodaran, 1997), crustaceans (e.g. Sheehy, 1989;Wahle et al, 1996;Medina et al, 2000;Bluhm et al, 2001a,b) and vertebrates (Eldred et al, 1982). This supports the view that the connective tissue granules in E. exalbida are lipofuscin.…”
Section: Is the Substance Found In E Exalbida Lipofuscin?supporting
confidence: 72%
“…The results of these studies indicated that a blue fluorescent compound, possibly consisting of lipids, was the source of lipofuscin autofluorescence in tissues. However, it has also been shown that blue fluorescence can be induced artifactually through manipulations of the organic extract (e.g., light irradiation and chromatographic processes) (Eldred et al 1982;Eldred and Katz 1989;Kikugawa et al 1994). Recently, a series of reports has demonstrated that a lipofuscin-like compound is extractable by aqueous but not by organic solvents (Kikugawa et al 1994(Kikugawa et al ,1995(Kikugawa et al ,1997.…”
Section: Discussionmentioning
confidence: 99%
“…Retinal age pigments, or lipofuscin granula, contain the fluorophores that accumulate with age and that are thought to represent a biomarker for cellular aging (1). Lipofuscin results from an incomplete degradation of altered material trapped in lysosomes (2) and the accumulation of lipofuscin is related to an increased risk of choroidal neovascularization (CNV) 2 due to age-related macular degeneration (AMD) (1,2).…”
mentioning
confidence: 99%
“…Lipofuscin results from an incomplete degradation of altered material trapped in lysosomes (2) and the accumulation of lipofuscin is related to an increased risk of choroidal neovascularization (CNV) 2 due to age-related macular degeneration (AMD) (1,2). AMD is a leading cause of legal blindness in developed countries (3), and even with the recent advent of several treatment options (4), treatment of AMD remains difficult (5).…”
mentioning
confidence: 99%